Efek Sari Daun Sereh Wangi Terhadap Kualitas Semen Babi Landrace X Duroc Dalam Pengencer Tris-Kuning Telur - jourvan manasye marabijala; Wilmientje Marlene Nalley; Thomas Mata Hine; Alvrado Bire Lawa (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2025)
The purpose of this research is to evaluate the level of lemongrass leaf extract added to Tris-egg yolk diluent to ensure that the spermatozoa quality of landrace x duroc crossbred boars is maintained during storage. In this study, fresh semen was used from 1.5 yearsold landrace x duroc crossbred boars that were in healthy condition and had been trained to collect semen. To conduct this research, completely randomized design was used, consisting of six treatments and five replications, namely: T0= Tris-egg yolk, T1= Tris-egg yolk + lemongrass leaf extract 0,5%, T2= Tris-egg yolk + lemongrass leaf extract 1,0%, T3= Tris-egg yolk + lemongrass leaf extract 1,5%, T4= Tris-egg yolk + lemongrass leaf extract 2,0%, T5= Tris-egg yolk + lemongrass leaf extract 2,5%. After dilution, the semen was stored in a styrofoam box at a temperature of 18-20°C. Four variables were tested: motility, viability, abnormality, and sperm survival. These variables were analyzed using a variability test and Duncan's analysis. The findings revealed that the spermatozoa quality of treatment P2 at the 60th hour of observation displayed a notable distinction. (P<0.05) from other treatments. The motility value was 54.00%, the viability was 64.10%, the abnormality was 5.70%, and the sperm survival was 67.68 hours. This study found that adding lemongrass leaf extract to Tris-egg yolk diluent at a level of 1.0% improved the quality of landrace x duroc crossbred boars spermatozoa.